MICROBIAL FUEL CELL BERBASIS YEAST Saccharomyces cerevisiae - Ummy Mardiana (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2015)
Nowadays, many research on energy production have been intensively developed. MFCs are known as green technology is a new opportunity for the sustainable production of energy by converting chemical energy to electrical energy by biodegradation using microorganisms as biocatalysts.We propose a microbial fuel cellwhich Baker’s yeast Sacharomyces cereviceae as biocatalyst, whereas K3Fe(CN)6 was used as electron acceptor in the catholyte. Chronoamperometry has been selected as method to determination of the MFC operational characteristics.Several conditions to optimize current and power density of the MFC has been observed. The effect of yeast preparation, tempetarature, stability of yeast and have been characterized and prepared for MFC. The effect of yeast preparation could achieve enhancement of power output around 40%, meanwhile the optimum temperature has been achieved at 400C. The stability of yeast has been obtained during 3 weeks of observation. The MFC operation has been built during 7 days of running and the maximum current density produced by the cell was 92.5 mA.m-2 . Further developments are in progress to improve performance and power output to make yeast fuel cells applicable as one of promising biotechnology for desalination and water treatment. Keywords: Microbial fuel cell (MFC), Microbial desalination cell (MDC) Sacharomycescereviceae, biocatalyst, electrodialysis, desalination